DESIGN OF A SINGLE-STAGE AXIAL POWER TURBINE IN AN ULTRA-MICRO GAS TURBINE ENGINE - Solissa, Rizal Gidion; Hartono, Firman; Al Gifar, Muhamad Maris (Jurnal Rekayasa Mesin, 2025)
Today's electrical energy needs require several alternative power and electrical energy storage. One system that can be developed to meet these needs is an ultra-micro gas turbine. The single-stage axial power turbine is designed to drive a 182.574 KV BLDC electric motor generator with 50% efficiency at 10000 rpm which will produce 600 watts of power with a turbine diameter of 10-20 cm. The utilization is based on the exhaust gas from the turbine on the GT2052 turbocharger which has an efficiency value of 70%. The design is done by free fortex analytical method and gas flow simulation using computational fluid dynamic Ansys CFX. To be able to produce the target power for the BLDC electric motor, the single-stage axial power turbine designed with CFD simulation produces a power of 1830.59 watts with an air mass flow of 0.166 kg/s, a pressure ratio of 1.06, an efficiency of 80.7%.